Generation of a family of Pearcey beams based on Fresnel diffraction catastrophes. (4th September 2015) - Zhijun, Ren; Chaofu, Ying; Hongzhen, Jin; Bo, Chen
Abstract: Based on the theory of differential geometry and Fresnel diffraction catastrophes, we theoretically prove that the cusped caustic of Pearcey beams are the evolute of a parabola and thus identify the key factor determining the optical structure of Pearcey beams. We numerically simulate and experimentally generate a family of Pearcey beams with various optical topological structures using different parabolas. We then investigate their optical structures and propagation properties.